Using modified IPA to define quality improvement strategies: A study of air-conditioning industry in Taiwan. Issue 2 (14th March 2016) - Ho, Li-Hsing; Chang, Pi-Yun; Yen, Tieh-Min
Abstract : Purpose: – The purpose of this paper is to propose a modified Importance-Performance Analysis (IPA) model and calculates the performance of quality characteristic for the purpose of defining quality improvement strategy. Design/methodology/approach: – This study developed modified IPA by introducing the Mahalanobis Distance and multiple regression analysis to evaluate the performance gap and implicit importance of quality characteristics. This paper used a large air-conditioning manufacturer in Taiwan as the case analysis and study targets. It discussed and validated the modified IPA analytical results by studying case history and market analysis. Findings: – Through the case study, the quality characteristics of air-conditioning product and service needed to be improved immediately are Green product (Q3) and Repair service (Q10), and the Price (Q11) and Serviceability (Q2) could be kept or enhanced to win the market competitive advantages. Originality/value: – This study developed a modified IPA to help organization identifying key quality characteristics of product and service, and choosing its improvement strategies to win the market competitive advantages effectively.